SEJARAH (PENDIDIKAN) ISLAM MODERN DALAM PERSPEKTIF IBRAHIM M. ABU-RABI’ - Nurul Mubin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2018)
The debate among Western academics, US politicians and security councils has intensifiedfollowing similar attacks, although not as devastating as the September 11 tragedy, somesee political Islam, especially regarding the relationship between Islam and democracy,at least divided into two major currents; the first group is a group that concludes thatIslam does not oppose democracy, the second group is a group that views Islam asopposed to democracy. This group assumes that the fundamental values of Islam arevery compatible with democracy. Islam is not anti-democratic, but between Islam anddemocracy can live side by side. Not only are Western thinkers who have views like this,not a few among Islamic scholars have this view. Ibrahim M. Abu Rabi 'in the theme of hisarticle entitled